2013
DOI: 10.1038/ejcn.2013.197
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids: a review of the effects on adiponectin and leptin and potential implications for obesity management

Abstract: An increase in adiposity is associated with altered levels of biologically active proteins. These include the hormones adiponectin and leptin. The marked change in circulating concentrations of these hormones in obesity has been associated with the development of insulin resistance and metabolic syndrome. Variations in dietary lipid consumption have also been shown to impact obesity. Specifically, omega-3 fatty acids have been correlated with the prevention of obesity and subsequent development of chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 117 publications
9
45
1
Order By: Relevance
“…Previously, it has been suggested that omega-3 may be effective in the prevention of obesity and reducing weight, 41 and by considering the positive association between weight and leptin, we expected that we would observe a reduction of leptin level as well. However, this effect has only been observed in non-obese individuals.…”
Section: Discussionmentioning
confidence: 78%
“…Previously, it has been suggested that omega-3 may be effective in the prevention of obesity and reducing weight, 41 and by considering the positive association between weight and leptin, we expected that we would observe a reduction of leptin level as well. However, this effect has only been observed in non-obese individuals.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast with the v-6 PUFAs, the v-3 PUFAs are usually attributed anti-inflammatory effects, particularly when considering the metabolic syndrome, type 2 diabetes, and cardiovascular disease (Calviello et al, 2013;Gray et al, 2013;Liu et al, 2013;Robinson and Mazurak, 2013;Pinel et al, 2014;Yates et al, 2014). Despite early positive reports of the benefits of supplementing diets with fish oils on cardiovascular outcomes, larger and better controlled clinical trials have failed to reveal any clear clinical benefit.…”
Section: G Metabolism and Diabetesmentioning
confidence: 99%
“…Rats on the HFC diet and fructose drinking water had blood insulin and leptin levels twice as much as those on the LFC improves insulin sensitivity. Dietary supplementation of n-3 PUFA, in particular EPA and DHA, increases the serum concentration of adiponectin in humans and animals (Gray et al, 2013;Sabour et al, 2015). Recent reports demonstrated that replacing saturated fatty acids with n-3…”
Section: Shrimp Oil Improved Serum Lipid Profilementioning
confidence: 99%